Analisis Ilmu Falak Tentang Pelarangan Waktu Salat - Novegar, Istiqfar; Rahmatiah,HL,; Wijaya, Abdi (HISABUNA: Jurnal Ilmu Falak, 2023)
Abstract: Prayer is one of the conditions for the validity of prayer, because not all prayer times end is the beginning of the next prayer time. Because there are times when we are forbidden to pray, but in fiqh the times that are forbidden to perform prayers are explained uncertainly, only natural phenomena are explained, therefore this is important to know because we should not pray at the wrong time. forbidden, then what happens in our worship does not get a reward but is makruh which is close to haram. The times of prayer have been hinted by Allah swt. In the verses of the Qur'an, which was later explained by the Prophet. in this case it is an obligation to perform prayers, related to the times that have been determined. As mentioned in the word of Allah swt Qs. An-nisa' verse 103. Prayer is one of the acts of worship that Allah swt directly revealed to the Prophet Muhammad without the angels, when he was carrying out his Isra' and Mi'raj, which was actually 50 times and then processed into 5 obligatory prayers. , the sentence for the fard prayer is actually already from the collection of prayers of the previous prophets, namely prayer. It's just that the prayer times indicated by the Qur'an and hadith are only natural phenomena, which if you don't use astronomy, of course you will have difficulty determining the start of prayer times. The criteria for the time it is forbidden to perform prayers according to the concept of fiqh and formulate it in astronomy so that it can be ascertained about the certainty of the time. The height of the sun at times that are prohibited for performing prayers is adjusted based on the concept of fiqh. And the results of the calculation when the sun rises is at 05:37 with the sun's height -1º04'43.51, while the beginning of special time is when the sun is right at its culmination, which is 11:52, and the beginning of the time when it sets is at 18:03 with the sun's height is 1º04'43.51. Keywords: Astrology, Prohibition, Prayer Times.